2021
DOI: 10.1002/cam4.4351
|View full text |Cite
|
Sign up to set email alerts
|

Nonmetastatic breast cancer patients subsequently developing second primary malignancy: A population‐based study

Abstract: Background With life span extending, breast cancer (BC) survivors may face the possibility of developing second primary cancer (SPC) and considerably shorten survivorship. However, little is known about multiple primary cancer (MPC) patients with nonmetastatic breast cancer as a first primary malignancy (BCFPM). Methods Here, we retrospectively analyzed data on cancer survivors with BCFPM diagnosed between 2010 and 2015 from the Surveillance, Epidemiology, and End Results (SEER) database. The prognostic factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
(60 reference statements)
1
3
1
Order By: Relevance
“…The risk of second primary BC was even lower in NMBC patients. However, our results contradict previous studies which reported an increased risk of SPCs in NMBC patients ( 17 , 18 ). It is important to note that previous studies failed to incorporate the peculiarities of regional lymph nodes MBC patients and were classified in the same “non-metastatic” category.…”
Section: Discussioncontrasting
confidence: 99%
“…The risk of second primary BC was even lower in NMBC patients. However, our results contradict previous studies which reported an increased risk of SPCs in NMBC patients ( 17 , 18 ). It is important to note that previous studies failed to incorporate the peculiarities of regional lymph nodes MBC patients and were classified in the same “non-metastatic” category.…”
Section: Discussioncontrasting
confidence: 99%
“…A similar study was published by Bao et al. on female breast cancer patients ( 31 ). Mellemkjær et al.…”
Section: Discussionsupporting
confidence: 72%
“…The descriptive epidemiology of second primary cancer among survivors at 5, 10, and 15 years is reported to be 3.6%, 8.2%, and 13.9%, respectively ( 13 ), and patients less than 50 years of age (also premenopausal ages) are at a higher risk of developing second cancer ( 10 , 12 ). Several population-based cancer registry studies have assessed the risk of second primary cancers among women diagnosed with primary breast cancer compared with the general population ( 10 , 12 , 14 – 18 ). Some studies have also examined the risk of developing second cancer based on the type of treatment ( 19 24 ), age difference ( 25 27 ), and family history ( 27 29 ).…”
Section: Introductionmentioning
confidence: 99%